Mapping the Research Landscape of Sustainable Tourism and Destination Competitiveness in Indonesia: A Bibliometric Study - Rifqi Asy'ari; Panji Alam Prabowo; Muhammad Fiqhri Arhaj (PROGRAM STUDI PARIWISATA SYARAH, FAKULTAS EKONOMI DAN BISNIS ISLAM, UNIVERSITAS ISLAM NEGERI MATARAM, 2026)
Purpose: This study aims to map the research landscape on Sustainable Tourism and Destination Competitiveness in Indonesia, analyze the development of publications, relationships between keywords, the evolution of research themes, and identify themes that still have opportunities for development. Method: The study used a bibliometric approach with Google Scholar data sources extracted through Publish or Perish version 8. Metadata was cleaned using OpenRefine and analyzed using VOSviewer through Network Visualization, Overlay Visualization, and Density Visualization. Of the 1,000 initial publications obtained, 616 journal articles met the criteria and were used as the research dataset. Result: The research findings indicate that the study of sustainable tourism and destination competitiveness in Indonesia has developed into a multidimensional field with strong links between destination management, innovation, technology, service quality, destination image, and tourist satisfaction. The analysis also indicates a shift in research focus toward sustainability, digital transformation, and destination governance. Meanwhile, themes such as sustainable tourism policy, community empowerment, local wisdom, and rural tourism still have relatively low research intensity, offering opportunities for future research. Contribution: This research contributes to the development of scientific knowledge by presenting a comprehensive bibliometric mapping of the conceptual structure, thematic developments, and research gaps in studies on Sustainable Tourism and Destination Competitiveness in Indonesia. The findings are expected to serve as a reference for researchers in identifying future research directions and support policymakers and destination managers in formulating evidence-based strategies for sustainable and competitive tourism development.